Bilateral Adrenal Myelolipoma, A Case Presentation and Brief Literature Review (Iranian Journal of Kidney Diseases, 2020)
As a rare and normally-benign and functionless tumor, primary adrenal myelolipoma comprises adipose tissue and myeloid cells, and its diagnosis is usually difficult owing to its asymptomatic nature. Imaging techniques can detect these masses in over 90% of the cases. CT scan is the most sensitive imaging technique, which can display the tissue nature of this tumor with a high resolution. The present case report involves a 45-year-old woman with bilateral adrenal myelolipoma diagnosed with imaging methods.